FEMINISME INDONESIA DALAM LINTASAN SEJARAH - Aliyah, Ida Hidayatul; Komariah, Siti; Chotim, Endah Ratnawaty (TEMALI : Jurnal Pembangunan Sosial, 2018)
This article studies the opinion of Muslim feminists on Islam and women empowerment. Using Indonesian history as the reference of being colonized, analytically the writer shows how these cultural and political problems placed Indonesian Muslim women into a kind of continuing struggle of independence. Having a careful consideration of Indonesian history and culture, the writer’s final idea was that Islam has a meeting point with feminism. It is suggested, then, that based on Indonesian Muslim history it should be acknowledged that Islam is compatible with the idea of progress for women.